Determination of two key parameters of a cohesive zone model for pipeline steels based on uniaxial stress-strain curve. (September 2016) - Wang, Y.J.; Ru, C.Q.
Highlights: A method is developed to estimate key parameters of cohesive-zone model based on stress-strain curve of a real material. Maximum traction is defined as the critical stress and cohesive energy is estimated from a tensile test simulation. Dynamic fracture behavior predicted well agrees with some known test data and previous related works. Abstract: It is widely believed that maximum traction of traction-separation law (TSL) and cohesive energy are the two key parameters of cohesive zone model (CZM). A method is presented in this paper to determine the two key CZM parameters for pipeline steels. The maximum traction of TSL is given by the critical stress defined based on damage at fracture point from the true stress-strain curve. And the other key parameter, cohesive energy defined as the area under the curve of TSL and usually considered as the critical J-integral, is estimated from a simple tensile test simulation. The two key CZM parameters obtained by the present method are validated for dynamic fracture of pipeline steels. Both load-displacement curves and crack tip opening angle (CTOA)-fracture speed curves showed that the two key CZM parameters determined by the present method are reasonable, and dynamic fracture behavior predicted based on the two predicted key CZM parameters well agree with some known test data and previous work.